One inch incision-mesh plug repair versus laparoscopic trans-abdominal preperitoneal repair of the primary indirect inguinal hernia: a prospective comparative study - Abdelhalim, Mohamed F. (International Surgery Journal, 2021)
Background: Management of inguinal hernia by minimally invasive incision and minimal dissection with optimal outcomes remains an unmet need for general surgeons. The most common hernia repair procedures are Lichtenstein hernioplasty and laparoscopic hernia repair; TAPP and TEP. The modification of mesh plug repair (MPR); one inch incision-MPR (OI-MPR); could achieve optimal outcomes comparable to that of laparoscopic hernia repair. The objective of the study was to assess OI-MPR approach for management of primary indirect inguinal hernia and its outcomes in comparison to laparoscopic TAPP repair. Methods: During the period from September 2017 to March 2019, 63 patients with indirect inguinal hernia were selected randomly to one of two groups; group-A included 35 patients underwent one inch incision-mesh plug repair (OI-MPR), group-B included 28 patients underwent laparoscopic TAPP. Results: The mean operative time of group-A was 31.74±4.74 min which was significantly shorter than that of group-B (81.22±7.44 min). The mean hospital stay duration in group-A was 0.57±0.18 day and in group-B, it was 1.18±0.39 day. The patients of group-A returned to normal physical activities earlier than the patients of group-B. The duration of postoperative pain was shorter and less severe in group-A than that of group-B. Regarding complications, there was no statistically significant difference found between both groups. Conclusions: One inch incision-MPR is a simple, feasible and cost-effective approach with low morbidities and low burden on the patients and the healthcare facilities.